Environmental justice and governance: Theory and lessons from the implementation of the European Union's habitats directive - Jouni Paavola (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
The paper investigates the role of justice in protected areas governance. The paper argues that protected areas governance faces a need to justify itself for the involved and affected interest groups in order to guarantee its legitimacy and effectiveness. The legitimacy of governance solutions is argued to rest on both distributive and procedural justice. On one hand, the distribution of beneficial and adverse consequences of protected areas governance must be justifiable and justified. On the other hand, decision-making regarding protected areas has to satisfy expectations regarding procedural justice. The paper exemplifies these arguments by analysing the experiences in implementing the European Union's Habitats Directive. The paper demonstrates how the lack of attention to distributive and procedural justice has resulted in conflicts which have delayed the implementation of the directive and have undermined its effectiveness.
Keywords: 330; environmental governance; Habitats Directive; justice; participation; protected areas; Naturschutzgebiet; Umweltrecht; Raumordnungsrecht; EU-Staaten